MANAJEMEN LABA, RETURN SAHAM, DAN KINERJA OPERASI SEBAGAI PEMODERASI - Farid Addy Sumantri; Purnamawati (Media Riset Akuntansi, Auditing & Informasi, 2013)
The purpose of this study was to determine the indications of the practice of earnings management at the time of the IPO, one year after the IPO, and two years after the IPO. This study also examined the effect of earnings management on stock returns and operating performance in moderating the relationship between earnings management and stock returns.The study sample comprised 33 firms that go public in the year 2007 to 2011 using a purposive sampling method. Earnings management is proxied by discretionary accruals using the Modified Jones Model, which used proxy for the stock return is cummulative abnormal returns (CAR), while for the company’s operating performance used proxy for the return on assets (ROA).The results showed that there were indications of earnings management at the time of the IPO, one year after the IPO, and two years after the IPO with a lower profit rate. No effect on earnings management is proxied by stock return cummulative abnormal returns (CAR). Operating performance of the company also can not moderate the relationship between earnings management with stock return.